Fatal community-acquired ribotype 002 Clostridium difficile bacteremia. (April 2017) - Dauby, Nicolas; Libois, Agnès; Van Broeck, Johan; Delmée, Michel; Vandenberg, Olivier; Martiny, Delphine
Abstract: Extra-colonic infections, and especially bacteremia, are infrequent manifestations of Clostridium difficile infection. C. difficile bacteremia is generally health-care associated and polymicrobial. We report the case of a patient on hunger strike that presented a C. difficile colitis and mono-microbial bacteremia on its admission to the hospital. Multilocus variable number tandem repeat analysis of stool and blood isolates indicated clonality. The strain was characterized as a ribotype 002, an emerging ribotype previously associated with high fatality rate. The patient received treatment by intra-venous amoxicillin-clavulanate and oral vancomycin but eventually died on the seventh day of admission with concomitant pneumonia and pulmonary embolism. Highlights: Clostridium difficile bacteremia is uncommon and usually health-care associated. We report a case of fatal community-acquired CDB associated with a C. difficile colitis in a patient on hunger strike. Multilocus variable number tandem repeat analysis of stool and blood isolates indicated clonality. The strain belonged to ribotype 002 which is an emerging cause of severe and health-care associated C. difficile infections. We hypothesize that severe malnutrition lead to dysbiosis and impaired mucosal immunity promoting translocation from the gut.